IMPLICATIONS OF GAS-LIQUID PHASE TRANSITIONS FOR ENDOGENIC ORIGIN OF HYDROCARBONS - Malyshev A.I. (My University, 2004)
Based on elementary molecular-chemical concepts, one can trace the evolution of the gaseous phase of an endogenic fluid at its temperature equilibrium with host rocks. As can be seen, the final result of this evolution consists in hydrocarbon formation within the hydrogen sulfide (point C) and carbon dioxide (point D) condensation zones.